A biaryl-cyclohexenone photoelectrocyclization/dearomatization sequence to substituted terpenes. (26th January 2023) - Satyanarayana Tummalapalli, K.S.; Zhao, Xuchen; Rainier, Jon D.
Abstract: Described here is the development of sequential cross-coupling, photoelectrocyclizations, and reductive dearomatizations of biaryl cyclohexenones as a means of synthesizing terpene skeletons. This methodology promises to provide insight that will enable us and others to use this approach to generate a variety of biologically active small molecules, including members of the abietane and morphinan skeletons. Graphical abstract: Image 1